Relationship between Religious Support and Major Depressive Episode for Adult Non-Medical Prescription Opioid Users and Non-Users. (17th February 2020) - Nugraheni, Suryadewi E.; Hastings, Julia F.
Abstract: Background: Non-medical prescription opioid use (NMPOU) is linked with poor mental health outcomes. Previous research has shown that religious support is protective for mental health. Objectives: To fill the gap in knowledge about how to assist NMPOU users decrease or prevent depression symptoms by incorporating religious support and to identify whether the suppressor model or the health effects model reflects the relationship between religious support and major depressive episode (MDE) for NMPOU users. Methods: Data from the 2016 National Survey on Drug Use and Health were analyzed for 42, 625 adults aged 18 years and older. Weighted binary logistic regression analyses were conducted using STATA 15 to examine the odds of NMPOU and religious support on MDE, all within the past year. Results: NMPOU was associated with increased odds of having a past-year MDE (OR = 2.99, 95% CI: 2.47, 3.62). Two significant associations were found among non-users: (a) between MDE and the importance of one's religious beliefs (OR = 0.78, 95% CI: 0.64, 0.94) and (b) between MDE and sharing one's religious beliefs with friends (OR = 0.66, 95% CI: 0.56, 0.78). However, the association of religious support and MDE among NMPOU users was not statistically observed. Conclusions: Religious support from friends and believing religious beliefs are essential in life appeared to be protective factors against MDE among non-users. Further research is needed to explore protective factors that can effectively address the association between opioid misuse and mental health and be incorporated into health interventions targeting the opioid epidemic.